3D Bioprinting Regulations: a UK/EU Perspective. (21st July 2017) - LI, Phoebe; FAULKNER, Alex
Abstract: This report introduces the challenges 3D bioprinting poses to the existing legal regime across bioethics, safety, regenerative medicine, and tissue engineering. We briefly review the 3D bioprinting technology and look into the relevant regulatory instruments for the pre-printing, printing, and post-printing stages. Special attention is paid to the applications of the EU Advanced Therapy Medicinal Products Regulation and the new Medical Device Regulation.